Decision Tree Menggunakan Algoritma C4.5 Untuk Analisa Kelayakan Pemberian Kredit - Yusuf, Diana; Bahri, Saeful; Larasati, Anggita (ITB Ahmad Dahlan Jakarta, 2021)
Data mining is a new technology that has been successfully applied in many fields. Many problems are solved by data mining algorithms as a supporter. Classification is one of the methods contained in data mining and not a few researchers who use the classification methods in solving problems. Credit analysis will be done with the digging data against existing data customer credits based on atribute with data mining algorithm. The algorithm C4.5 is itself a group of decision tree algorithm. This algorithm has input in the form of training and samples. Data mining technique used to classify loans with algorithm C4.5. Analysis and processing of data use applied tools of RapidMiner.